Overlapping Distribution of Orexin and Endocannabinoid Receptors and Their Functional Interaction in the Brain of Adult Zebrafish - Imperatore, Roberta; D’Angelo, Livia; Safari, Omid; Motlagh, Hamidreza Ahmadniaye; Piscitelli, Fabiana; de Girolamo, Paolo; Cristino, Luigia; Varricchio, Ettore; di Marzo, Vincenzo; Paolucci, Marina (Frontiers in Neuroanatomy, 2018)
Hypocretins/Orexins neuropeptides are known to regulate numerous physiological functions, such as energy homeostasis, food intake, sleep/wake cycle, arousal and wakefulness, in vertebrates. Previous studies on mice have revealed an intriguing orexins/endocannabinoids (ECs) signaling interaction at both structural and functional levels, with OX-A behaving as a strong enhancer of 2-arachydonoil-glycerol (2-AG) biosynthesis. In this study, we describe, for the first time in the brain of zebrafish, the anatomical distribution and co-expression of orexin OX-2R and endocannabinoid CB1R receptors, suggesting a functional interaction. The immunohistochemical colocalization of these receptors by confocal imaging in the dorsal and ventral telencephalon, suprachiasmatic nucleus, thalamus, hypothalamus, preoptic area and cerebellum, is reported. Moreover, biochemical quantification of 2-AG levels by LC-MS supports the occurrence of OX-A-induced 2-AG biosynthesis in the zebrafish brain after 3h of OX-A intraperitoneal (i.p.) (3 pmol/g) or intracerebroventricular (i.c.v.) (0.3 pmol/g) injection. This effect is likely mediated by OX-2R as it is counteracted by i.p./i.c.v administration of OX-2R antagonist (SB334867, 10 pmol/g). This study provides compelling morphological and functional evidence of an OX-2R/CB1R signaling interaction in the brain of adult zebrafish, suggesting the use of this well established vertebrate animal model for the study of complex and phylogenetically conserved physiological functions.